Keratoplasty Rejection After the BNT162b2 messenger RNA Vaccine. Issue 8 (August 2021) - Wasser, Lauren M.; Roditi, Eduardo; Zadok, David; Berkowitz, Liron; Weill, Yishay
Abstract : Purpose: The aim of this report was to report 2 patients who presented with acute corneal graft rejection 2 weeks after receiving the BNT162b2 messenger RNA (mRNA) vaccine for severe acute respiratory syndrome coronavirus 2. Methods: Case report. Results: Two men, aged 73 and 56 years, with a history of penetrating keratoplasty due to keratoconus were noted to have acute corneal graft rejection 2 weeks after receiving a first dose of the BNT162b2 mRNA vaccine. Both patients were treated with hourly dexamethasone 0.1% and oral prednisone 60 mg per day with prompt resolution of keratoplasty rejection. Conclusions: The BNT162b2 mRNA vaccine may be have been associated with a low-risk corneal graft rejection that responded well to topical and systemic steroids. Treating physicians should be aware of this potential complication and patients should be advised to report any visual changes after vaccination.